Isolation and Characterization of Kaempferol-7-O-methyl ether from Solenostemon monostachys (P.Beauv.) Briq. (Lamiaceae) - Baba, Haruna; Usifoh, Cyril O. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2014)
Solenostemon monostachys (Lamiaceae) is a common herb found in the southern part of Nigeria where it is used in the treatment of diabetes, tuberculosis, threatened abortion and other common ailments. Preliminary phytochemical screening has shown the presence of glycosides, flavonoids, tannins, saponins and anthraquinones. Phytochemical investigation of the dichloromethane extract of the leave, involving the use of flash chromatography and gel filtration on sephadex LH-20 was carried out and this has led to the isolation of kaempferol- 7-O-methylether.